STUDY OF CERAMIC FORMULATIONS FOR ELECTRICAL INSULATORS - Tejada, Víctor (2016)
The Peruvian company Cerartec S.A has developed ceramic-based electrical insulators for medium voltage lines. These products, ANSI 53-2 type (Spool and Guy Strain Insulators), are composed mainly of peruvian raw materials. Both formulation and process have an influence on residual porosities. Relevant parameters of formulation and process have been identified. In the investigated range, a linear relationship was drawn between porosities and flexural modulus of rupture. The new ceramic electrical insulators have been tested in terms of dielectric resistance, in dry and wet conditions.